2019
DOI: 10.1039/c8ra08861f
|View full text |Cite
|
Sign up to set email alerts
|

Microphase separation of a quadruple hydrogen bonding supramolecular polymer: effect of the steric hindrance of the ureido-pyrimidone on their viscoelasticity

Abstract: The supramolecular polymers based on 2-ureido-4[1H]-pyrimidone (UPy) with different structure were prepared and the effects of microtopography on the viscoelasticity were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…It has been in particular shown that even in high molecular weight polymer matrix (low UPy concentration) the phase separation exists and it contributes to stress relaxation mechanism, so the polymer chains do not behave like linear chains the Cates model hypothesized (Figure ). , Therefore, a plethora of studies reported the contribution of UPy stacking on polymer dynamics as an inevitable part of this sticker. , This is indeed a big disadvantage when comparing with theories, although in some studies this effect has not been truly addressed. , For instance, in one study by Binder et al on PnBA end-capped with THY and/or DAT the absence of a plateau in the frequency sweeps was related to the absence of phase separation . However, the corresponding slopes in the terminal regime did not show Maxwell behavior, similar to many studies where phase segregation was present and led to smaller terminal slopes instead of plateau formation .…”
Section: Sticker Positionmentioning
confidence: 78%
See 1 more Smart Citation
“…It has been in particular shown that even in high molecular weight polymer matrix (low UPy concentration) the phase separation exists and it contributes to stress relaxation mechanism, so the polymer chains do not behave like linear chains the Cates model hypothesized (Figure ). , Therefore, a plethora of studies reported the contribution of UPy stacking on polymer dynamics as an inevitable part of this sticker. , This is indeed a big disadvantage when comparing with theories, although in some studies this effect has not been truly addressed. , For instance, in one study by Binder et al on PnBA end-capped with THY and/or DAT the absence of a plateau in the frequency sweeps was related to the absence of phase separation . However, the corresponding slopes in the terminal regime did not show Maxwell behavior, similar to many studies where phase segregation was present and led to smaller terminal slopes instead of plateau formation .…”
Section: Sticker Positionmentioning
confidence: 78%
“…96,34 Therefore, a plethora of studies reported the contribution of UPy stacking on polymer dynamics as an inevitable part of this sticker. 97,98 This is indeed a big disadvantage when comparing with theories, although in some studies this effect has not been truly addressed. 99,100 For instance, in one study by Binder et al on PnBA end-capped with THY and/or DAT the absence of a plateau in the frequency sweeps was related to the absence of phase separation.…”
Section: Sticker Positionmentioning
confidence: 99%
“…Such phase separation has been found in different kinds of associating polymers, for example, in ionomers , or polymers with hydrogen bonding and even in some vitrimers . The clusters of functional groups can form a solid phase in the polymer melt , if their glass-transition temperature ( T g ) or melting temperature T m is higher than T g of the polymer backbone. The characteristic structure and morphology of these clusters can also be tuned with the architecture of the polymers .…”
Section: Introductionmentioning
confidence: 99%
“…In a similar system with a PBd core, nanofiber assemblies gradually disappear by increasing the size of the substituent on the sixth position from a methyl to a n-octyl. 101 Along the same lines, a low-frequency plateau emerges in unentangled side-chain UPy grafted poly(lauryl methacrylate) (PLMA) systems due to the aggregation of UPy dimers, which diminishes upon introduction of the bulky adamantyl group in the sixth position. 56 Surprisingly, this modification works oppositely in entangled systems.…”
Section: Materials Advancesmentioning
confidence: 94%